Shenling Baizhu San ameliorates non-alcoholic fatty liver disease in mice by modulating gut microbiota and metabolites - Chen, Dongliang; Wang, Yuanfei; Yang, Jianmei; Ou, Wanyi; Lin, Guiru; Zeng, Ze; Lu, Xiaomin; Chen, Zumin; Zou, Lili; Tian, Yaling; Wu, Aiping; Keating, Shelley E.; et al. (Frontiers in Pharmacology, 2024)
The prevalence of non-alcoholic fatty liver disease (NAFLD) and related mortality are increasing at an unprecedented rate. Traditional Chinese medicine (TCM) has been shown to offer potential for early prevention and treatment for NAFLD. This study examined the new mechanism of "Shenling Baizhu San" (SLBZS) in the prevention and treatment of NAFLD at the preclinical level.The male C57BL/6J mice were randomly divided into three groups: ND (normal diet), WDC (Western Diet+CCl4 injection) and WDC+SLBZS (SLBZS intervention). Body weight, energy intake, liver enzymes, pro-inflammatory factors and steatosis were recorded in detail. Meanwhile, TPH1, 5-HT, HTR2A and HTR2B were tested by qRT-PCR or ELISA. Dynamic changes in gut microbiota and metabolites were further detected through 16S rRNA gene and untargeted metabolomics.